45 Complete revascularisation is associated with improved survival after out of hospital cardiac arrest. (4th June 2021) - Kanyal, Ritesh; Pareek, Nilesh; Sarma, Dhruv; Bharucha, Apurva; Dworakowski, Rafal; Melikian, Narbeh; Webb, Ian; Shah, Ajay; MacCarthy, Philip; Byrne, Jonathan
Abstract : Introduction: Coronary artery disease (CAD) is common in patients with Out of Hospital Cardiac Arrest (OOHCA) but the clinical relevance of burden of CAD and evidence for revascularisation strategies in relation to outcomes and modes of death remains unclear. This study sought to assess the extent of CAD as defined by the SYNTAX score and prognostic value of complete compared with incomplete revascularisation by evaluating the SYNTAX revascularisation index (SRI) in patients with OOHCA. Methods: 619 patients with OOHCA were admitted at our centre between 1st May 2012 and 31st December 2017. 237 were excluded for having a non-cardiac aetiology or prior neurological disability. 398 patients were included into the study and of these 272 (xx%) had early coronary angiography and were included in the final analysis. The baseline SYNTAX score (bSS) and residual SYNTAX score (rSS) were determined from the coronary angiograms by a blinded cardiologist. Patients were subdivided into 4 subgroups according to quartiles of the baseline syntax score (bSS) of 0, Group A: 1-10, Group B: 11-20 and Group C: ≥21. Complete revascularisation was defined as SRI of 1 and incomplete as SRI <1 where the SRI=(1-[rSS/bSS])×100 ( figure 1 ). Results: Patients with a bss of 0 were younger, more likely to be female with, had less shockable initial arrest rhythms and worse lactate and pH on arrival than those with bss>0. Patients with bss>0 (i.e. those with coronary artery disease) had similar cardiac arrest circumstances in terms of rates of witnessed, bystander CPR and shockable rhythms. Admission metabolic status reflected by pH and lactate and rates of ST elevation/LBBB were also identical for all three bss groups. However, LVEF on admission decreased significantly as coronary complexity increased (P<0.0001). While early angiography was more preferentially performed in those with higher coronary complexity, paradoxically, those with bss 1-4 had highest rates of culprit lesions which was reflected in higher rates of PCI ( table 1 ). Of the 273 patients who had PCI, 125 (45.8%) had complete revascularisation (CR) compared with 54.2% with incomplete revascularisation (IR). Complete revascularisation was most likely to be achieved in as the coronary complexity reduced (Group A-10-71.1%, Group B 41.1%, Group C- 23.3%). There was no difference in rates of cardiogenic shock between both groups (CR 61.1% vs. IR 69% p=ns), but patients with complete revascularisation were younger (58.8 vs 67.8, p <0.0001) with lower rates of hypertension previous coronary artery bypass graft (CABG) (16.2% vs 3.2%, p≤0.0001). Admission metabolic status was identical between both groups.Complete revascularisation was associated with decreased mortality at 30 days (45.9% vs 34.4%, p =0.049) and 12 months (49.3% vs 35.2 %, p=0.022). The lower mortality rate in CR was driven by lower cardiac deaths but this was not statistically significant (22% vs 7%, p=0.1) ( figure 2 ). Conclusions: Complete revascularisation in a primary coronary aetiology OOHCA group is associated with reduced early and long-term mortality, which may be driven by a reduction in cardiac deaths. Prospective randomised trials in this population are warranted. Conflict of Interest: None